Violence and Bullying Incidents Reported by School Counselors: The Efficacy of Counselors and Preventive and Interventional Approaches - Zeynep Deniz Yondem (European Scientific Journal, ESJ, 2016)
This study aims to determine the frequency of violence and bullying reported by Turkish school counselors and examines their perceived efficacy and preventive and interventional approaches using a qualitative/quantitative mixed method. Counselors reported the high frequency of different violent incidents (occurring between students, inflicted by families and inflicted by teachers) as recorded or in particular non-recorded. The frequency of family violence is higher in middle schools than high schools. All bullying frequency sub-types were high, physical bullying especially so. The frequency of physical, verbal and sexual bullying was significantly higher in middle schools. Trained and untrained counselors do not perceive efficacy as sufficient; they applied limited preventive and interventional studies, focusing on students rather than families or school personnel.